Primary renal mucinous adenocarcinoma masquerading as a giant renal cyst: a case report - Zeng, Hong; Zhang, Mengni; Xie, Yandong; Wang, Minghao; Dai, Jindong; Zhu, Xudong; Zeng, Yuhao; Xu, Nanwei; Huang, Peng; Zhao, Jinge; Sun, Guangxi; Zeng, Hao; et al. (Frontiers in Oncology, 2023)
Mucinous adenocarcinoma of the kidney is rarely reported in the literature. We present a previously unreported mucinous adenocarcinoma arising from the renal parenchyma. A 55-year-old male patient with no complaints showed a large cystic hypodense lesion in the upper left kidney on contrast-enhanced computed tomography (CT) scan. A left renal cyst was initially considered, and a partial nephrectomy (PN) was performed. During the operation, a large amount of jelly-like mucus and bean-curd-like necrotic tissue was found in the focus. The pathological diagnosis was mucinous adenocarcinoma, and further systemic examination revealed no clinical evidence of primary disease elsewhere. Then the patient underwent left radical nephrectomy (RN), and the cystic lesion was found in the renal parenchyma, while neither the collecting system nor the ureters were involved. Postoperative sequential chemotherapy and radiotherapy were administered, and no signs of disease recurrence were observed during 30 months of follow-up. Based on a literature review, we summarize the lesion with rarity and the associated dilemma in preoperative diagnosis and treatment. Given the high degree of malignancy, a careful history analysis accompanied by dynamic observation of imaging and tumor markers is recommended for the diagnosis of the disease. Comprehensive treatment based on surgery may improve its clinical outcomes.